Synthesis of Bispidine-Based Prostate-Specific Membrane Antigen-Targeted Conjugate and Initial Investigations - Machulkin, Aleksei E; Petrov, Stanislav A; Kraynova, Maria D; Garanina, Anastasiia S; Egorova, Bayirta V; Timoshenko, Roman V; Vaneev, Alexander N; Erofeev, Alexander S; Priselkova, Anna B; Kalinin, Mikhail A; Aleksei V Medved′ko; Kalmykov, Stepan N; et al. (Organics (Basel), 2025)
Nowadays, PSMA ligands are widely used for radiotheragnostic purposes in prostate cancer. The synthesis of a PSMA-Bisp conjugate was developed and realized with good yield (overall yield ~58% for the last two steps). All newly synthesized compounds were characterized by physicochemical methods: 1H and 13C NMR, HRMS, and LCMS (for biologically tested samples). Subsequently, Bisp1 (diacetate bispidine ligand), Bisp-alkyne (bifunctional derivative of Bisp1), and its conjugate PSMA-Bisp were labeled by 64Cu in mild conditions. In vitro studies of the labeled conjugate [64Cu]Cu-PSMA-Bisp have shown great stability in model solutions. Finally, [64Cu]Cu-PSMA-Bisp was compared to the well-known PSMA-617 conjugate labeled with 64Cu and they showed similar stability in excess bovine serum (BVS), and at the same time, labeling PSMA-Bisp with 64Cu is characterized by extremely high kinetics in mild conditions, while labeling PSMA-617 with 64Cu requires heating (90 °C). Thus, this conjugate can be incredibly promising for nuclear medicine.